2020
DOI: 10.1101/2020.09.03.277459
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cellular and molecular phenotypes ofC9orf72ALS/FTD patient derived iPSC-microglia mono-cultures

Abstract: Background: A mutation in the C9orf72 gene is the most common genetic mutation of familial and sporadic ALS, as well as familial FTD. While prior studies have focused on elucidating the mechanisms of neuronal dysfunction and neurodegeneration associated with this genetic mutation, the contribution of microglia to disease pathogenesis in the ALS/FTD disease spectrum remains poorly understood. Methods: Here, we generated a new disease model consisting of cultured C9orf72 ALS/FTD patient-derived induced pluripote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 174 publications
(332 reference statements)
0
4
0
Order By: Relevance
“…In addition, loss of C9orf72 led to metabolic modifications and lysosomal accumulation in microglia, with agerelated neuroinflammation similar to C9orf72 ALS but not SALS patient tissue [68,69], further indicating that metabolic alterations in microglia contribute to neuroinflammation. Remarkably, AbGC are also characterized by an increased proliferation rate and reduced mitochondrial bioenergetics [70], associated with abundance of lipid droplets, as well as ER cistern dilatation when analyzed by electron microscopy [38].…”
Section: Energy Metabolism and Metabolic Reprogramming In Alsmentioning
confidence: 91%
“…In addition, loss of C9orf72 led to metabolic modifications and lysosomal accumulation in microglia, with agerelated neuroinflammation similar to C9orf72 ALS but not SALS patient tissue [68,69], further indicating that metabolic alterations in microglia contribute to neuroinflammation. Remarkably, AbGC are also characterized by an increased proliferation rate and reduced mitochondrial bioenergetics [70], associated with abundance of lipid droplets, as well as ER cistern dilatation when analyzed by electron microscopy [38].…”
Section: Energy Metabolism and Metabolic Reprogramming In Alsmentioning
confidence: 91%
“…[5][6][7] Interestingly, neither our study [5] nor Lorenzini et al [7] found substantial differences in unstimulated C9orf72 mutant microglia compared to controls by RNA sequencing, and baseline key inflammatory marker expression, such as IL1B or IL6, was unchanged. [5][6][7] These findings suggest that the mere presence of the C9orf72 HRE does not inherently skew microglia towards a pro-inflammatory phenotype compared to control cells.…”
Section: C9orf72 Mutationsmentioning
confidence: 68%
“…Although the role of neurochemical pathways in microglia has been extensively studied, the mechanoreceptors that regulate microglial function remain largely unexplored. A very recent study used hPSC-derived MGLs to study PIEZO1, a mechanotransduction ion channel [120] . They found that PIEZO1 orchestrated the clearance of Aβ by improving phagocytosis, survival, and lysosomal activity.…”
Section: Alzheimer's Diseasementioning
confidence: 99%